Development of an Interactive E-Module Based on Google Sites to Support Chemistry Learning on Molecular Shape Material - Insani Indah Sari; Bayu Saputra; Annisa Meristin (Jurnal Evaluasi dan Pembelajaran, 2026)
Students face difficulties visualizing abstract molecular geometry concepts because current teaching materials lack 3D modeling support. To overcome this, this research aims to develop a valid, practical, and effective Google Sites-based e-module for learning molecular geometry. This study applied the Research and Development (R&D) method using Thiagarajan's 4D model. Data collection instruments included expert validation questionnaires, teacher perception surveys, student response questionnaires, pretest-posttest assessments, and learning observation sheets. The e-module's feasibility was assessed by expert lecturers and chemistry teachers. Practicality data were gathered through chemistry teachers' perceptions, observer sheets, and questionnaires from 31 eleventh-grade students. Effectiveness data were collected involving the same 31 eleventh-grade subjects. Expert validation results showed average percentage s of 87.73% for media and 86.5% for material, indicating the e-module is valid with "very high" criteria. During the limited trial phase, teacher and student perceptions scored 90.5% and 85.73%, demonstrating the e-module's practicality with "very high" criteria. The product's effectiveness in learning is evidenced by an average student N-gain score of 0.54 (moderate category). Based on these results, the developed e-module is declared feasible, practical, and effective for use as an educational medium.